2017
DOI: 10.21608/jssae.2017.38244
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Effect of Foliar Fertilization of Fe, Zn and Rates of P Fertilization on Growth and Yield of Cowpea

Abstract: At the Experimental Farm of Faculty of Agriculture, El-Mansoura University, Egypt, a field experiment was carried out, to investigate the effect of zinc and iron individually or mixed as foliar application on cowpea plant growth, chemical composition, yield and its components as well as availability of nutrients in the soil, all that under phosphorus application effect. The experiment was laid out in split plot design with three replicates, assigning twelve treatments consisting of three levels of phosphorus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Additionally, the vital roles of Fe on nodulation and consequently achievement in nitrogen fixation, its roles in heam and non heam enzymes, as a component of photosynthetic pigments as well as in photo assimilation process that was reflected on broad bean plant growth. Furthermore, the obtained results are coinciding with those reported by many researchers (Oliveira et al, 2017;Fouda and Abd-Elhamied, 2017;Nafady et al, 2018;Pereira et al, 2019). Finally, Abd-Alla et al, (2014) found increases in dry matter accumulation of shoots and roots of faba bean which inoculated with AMF and R. leguminosarum in alkaline soil.…”
Section: Disussionsupporting
confidence: 88%
“…Additionally, the vital roles of Fe on nodulation and consequently achievement in nitrogen fixation, its roles in heam and non heam enzymes, as a component of photosynthetic pigments as well as in photo assimilation process that was reflected on broad bean plant growth. Furthermore, the obtained results are coinciding with those reported by many researchers (Oliveira et al, 2017;Fouda and Abd-Elhamied, 2017;Nafady et al, 2018;Pereira et al, 2019). Finally, Abd-Alla et al, (2014) found increases in dry matter accumulation of shoots and roots of faba bean which inoculated with AMF and R. leguminosarum in alkaline soil.…”
Section: Disussionsupporting
confidence: 88%
“…Statistical analyses of data in Table 2, revealed that addition of significantly Integrated nutrients with seed coating by Gaucho increased chlorophyll a, b , a + b and carotene contents in cowpea leaves . Fouda and Abd-ELhamied (2017) found that foliar application with (Zn+Fe) under 100% P-fertilization resulted the highest values of chlorophyll a, b and a + b contents in cowpea leaves .…”
Section: Photosynthetic Pigments and Vegetative Growth Characteristicsmentioning
confidence: 91%
“…These results are in line with those found by . Knany et al(2009) El-Gizawy andMehasen(2009) and Fouda and Abd-Elhamied (2017).…”
Section: -Micro Elementsmentioning
confidence: 97%
“…of branches and pods/plant, 100-seed weight, seed yield/plant, seed and straw yields/fed, and protein%,) . Fouda and Abd-Elhamied(2017) demonstrated that treatment (foliar application with Fe) significantly increased plant height (cm) , No. of branches/plant, No.…”
Section: Introductionmentioning
confidence: 99%